Tragic Downfall: A Literary Significance of Macbeth and Julius Caesar - Ragos, Marie Jo Tess; Tenedero, Cynic (English Department of Faculty of Tarbiyah and Teacher Training, 2025)
This paper examined Julius Caesar and Macbeth as a tragic play written by William Shakespeare. In particular, this work of art deals briefly with the error of judgment which inevitably led to the tragic downfall of the characters particularly the protagonist in each play. This study utilized the qualitative research using objective approach and textual analysis. The researchers incorporated ideas from literary device called Hamartia by Aristotle, and the formalistic approach. This gives emphasis to the error of judgment of the characters found in two major plays of Shakespeare and show that this error has to do with their downfall and its implication to teaching literature. In the play Macbeth, the focus is on the ambition of the protagonist of becoming a king, and being too ambitious led him to danger while Julius Caesar’s error of judgement was his pride, arrogance and individual quest for power, self-priority and use of popularist tactics to further own political gains which led to political and military leadership. With all the good and horrible deeds of the characters in the play, the cause of the tragic end of the protagonist must be emphasized in the classroom discussions, since it is indeed timely and relevant for the readers to analyze how the sequence of the events changes from the state of happiness to a state of misery.